Factors Influencing Student Parents' Acceptance of the COVID-19 Vaccine - Arianti, Diana; Susanti, Amelia (Journal of Health Sciences and Epidemiology, 2023)
The COVID-19 pandemic has caused widespread destruction, including in Indonesia. Various efforts have been undertaken to combat the pandemic caused by COVID-19. Among them is immunization. However, the general population's acceptance of the COVID-19 vaccination is questionable. Due to the availability of multiple vaccines against COVID-19, there is confusion regarding the efficacy and safety of individual vaccines, particularly among students. The primary objective of this study was to determine the reception of the COVID-19 vaccine among the parents of students. From March to August 2022, a cross-sectional survey was conducted at Padang Elementary School No. 11. Respondents for the technique of purposive sampling are the parents of 68 students. The survey data were analyzed using SPSS version 25.0. Using the Chi-square test, the relationship between socio-demographics and COVID-19 vaccine acceptance was analyzed. According to the findings of the study, approximately 51.5% of parents reject the COVI-19 vaccine for their offspring. There is a significant correlation between education level (p-value = 0.035), knowledge level (p-value = 0.000), and attitude (p-value = 0.000) and acceptance of the COVID-19 vaccine, as determined by a statistical test. The acceptance of the COVID-19 vaccine is significantly affected by parents' knowledge of vaccines. The government or authorized organizations must enhance and target the dissemination of accurate information about vaccines.